EWaS3 2018 2018
DOI: 10.3390/proceedings2110628
|View full text |Cite
|
Sign up to set email alerts
|

Wave-Current Interactions and Infragravity Wave Propagation at a Microtidal Inlet

Abstract: Recent studies have shown that wave blocking occurs at river mouths with strong currents typically preventing relatively short period sea and swell waves from propagating up the river. However, observations demonstrate that lower frequency waves, so-called infragravity waves, do pass through and propagate up the river, particularly during storm events. We present observations from the Misa River estuary of infragravity wave propagation up the river during storm conditions. A model of the complex nonlinear inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
(22 reference statements)
3
16
0
Order By: Relevance
“…Previous work has identified that more energetic ocean wave conditions correspond to an increased wave climate within IOCE (Bertin and Olabarrieta, 2016; Williams and Stacey, 2016; Melito et al ., 2018). This is consistent with our findings (Table III).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has identified that more energetic ocean wave conditions correspond to an increased wave climate within IOCE (Bertin and Olabarrieta, 2016; Williams and Stacey, 2016; Melito et al ., 2018). This is consistent with our findings (Table III).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we expect uncertainties in the water surface elevation imposed at the downstream boundary of the hydraulic model domain to strongly influence extreme water levels in the downstream reach. Wave contributions, such as wave setup and wave propagation, are also not directly represented by the BN but can strongly influence water levels [88][89][90]. While this study can be improved by using complementary data at these stations, this typically requires dedicated and extensive studies to properly capture complex coastal and hydrological processes [64,91,92] and is left for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…studies (Brocchini et al, 2017;Melito et al, 2018aMelito et al, , 2019 The EsCoSed field campaign has also provided useful information on the seabed morphology at the river mouth, highlighting the formation of large deposits/bars (blue in the right panel of figure 18) and scours holes (red in the right panel of figure 18). The sand deposits are found to be at a typical location, i.e.…”
Section: River Mouthsmentioning
confidence: 99%
“…Other recent field observations support the role of river mouths and the upriver propagation of IG waves. Among these, notable are the EsCoSed and MORSE project studies (Brocchini et al, ; Melito et al, , ) performed at the mouth of the Misa River (Italy, see Figures and ), located at a microtidal site (RTR < 3) with a dissipative‐to‐intermediate beach (5 < Ω < 20).…”
Section: Wave Forced‐dynamics For Three Fundamental Subsystems: Sandbmentioning
confidence: 99%
See 1 more Smart Citation